PENGARUH PENDIDIKAN FORMAL ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM PESERTA DIDIK MTS PONPES AL-HASANAH BENGKULU TENGAH - Yulia Refyani (IAIN Bengkulu, 2018)
The purpose of this writing is to know the influence of formal education of parents on learning achievement, to know the influence of learning motivation on learning achievement and to know the influence of formal education of parents and learning motivation on learning achievement of Islamic education students of MTs Ponpes Al-Hasanah Bengkulu Tengah. The method used in this research is quantitative research method, This research type is non experimental quantitative research. Techniques of collecting research data through questionnaires, interviews, observations, and documentation. The data analysis techniques in this study by using multiple linear regression analysis with the help of computer program SPSS version of Win- dows 16.0. The results of this study indicate that there is influence between formal parent education and learning motivation on learning achievement of Islamic religious education students of MTs Ponpes Al-Hasanah Central Bengkulu. The influence of for- mal education of parents on learning achievement of Islamic religious education students of MTs Ponpes Al-Hasanah Bengkulu The middle is 7.8%, while the remaining 92.2% is influenced by other variables other than the formal education of the parents. Furthermore there is a significant influence between learning motivation on learning achievement of Islamic religious education students of MTs Ponpes Al-Hasanah Central Bengkulu. The influence of learning motivation on learning achievement of Islamic religious education in MTs Ponpes Al-Hasanah Bengkulu Tengah is 27,3%, while the rest 72,7% is influenced by other variable beside motivation variable. Influence of parent formal education and learning motivation together learning achievement of Islamic education student of MTs Ponpes Al-Hasanah Bengkulu Tengah is equal to 34,7% while the rest is 65,3% influenced by other variable besides formal education variable of parent and motivation to learn.